Effect Of Dichlorvos On Serum Enzymes Of Poultry Birds - S.P.S. BISHT,; RAVI KUMAR B.V.V,; PRAVEEN. B,; RAJAKUMAR.V,; S. R. MISHRA, (International Journal of Pharma and Bio Sciences, 2012)
Dichlorvos is an organophosphate directly acting cholinesterase AChE inhibitor that has been commercially manufactured and used throughout the world as an insecticide. The present investigation was aimed to study the hepatotoxic effect of Dichlorvos at different dosages by estimating ASAT and ALAT enzyme levels in serum and the effect of Dichlorvos on weight gain of poultry birds. Dichlorvos was mixed with edible refined oil to prepare the feeding solution in the concentrations of 0.5 and 0.75 mg/kg body weight and fed to 18 birds in three groups for seven consecutive days. Birds treated with 1ml of refined oil Gr. 1(Control), 0.75ml of dichlorvas solution @ 0.5 mg/kg body weight (Gr II a) and with 0.50 ml of dichlorvas solution @ 0.75 mg/kg body weight (Gr II b) .The Gr II a and GrII b showed a rapid rise in serum ASAT and ALAT levels and gained weight after 5th week of age indicating the hepatotoxic effect of Dichlorvos.